A FPGA implementation of a LMS adaptative algorithm for smart antenna arrays - Castellanos Hernández, Javier Alexander; Sandoval Ruiz, Cecilia Esperanza; Azpúrua Auyanet, Marco Aurelio (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This paper presents a design of an adaptive algorithm, proposed for applications in arrays of antennas with adjustable weight. This algorithm was selected because of its simplicity, efficiency and performance; which makes it idoneous to be implemented on a reconfigurable hardware device. The methodology developed begins with the design of the study case and the analysis of the LMS algorithm in the adaptive control of the radiation pattern for the four element antenna array, using MATLABâ„¢ v.7.6., then the definition of the model, the components, the description of the behavior using the syntax in VHDL for the design on a FPGA device, using the ISE 10.1 Xilinx tool. Finally, the validation of the designed circuit is presented through simulations using ModelSim 5.7. Resulting in synthesis reports resources used in the design developed.